Peningkatan Keterampilan Menulis Ringkasan Teks Eksplanasi Menggunakan Model SQ3R Berbantuan Mind Mapping Pada Siswa Kelas V SDN - Esa Savira Salsabila; Titis Angga Rini; Putri Mahanani; Esa Savira Salsabila; Titis Angga Rini (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: This research aims to improve the ability to write an explanatory text summary using the SQ3R model with the aid of mind mapping. This research is a Classroom Action Research (CAR). This study uses the Arikunto cycle in two cycles. Data collection techniques in this study were observation, interviews, tests, documentation, and field notes. The subjects of this study were students of class 5C SDN Polehan 2 Malang City. The research instrument used teacher and student observation instruments, interview instruments, and test instruments. Data analysis used quantitative and qualitative descriptive analysis. The average percentage of teacher activity from the first cycle was 83.35 percent to 95 percent in the second cycle. The percentage of learning outcomes in pre-action skills is 31.81 percent. The percentage of skill learning outcomes in the first cycle was 86.36 percent, in the second cycle it increased to 90.9 percent. The aspect of attitude in the first cycle is still lacking in the aspect of self-confidence because students are still shy and do not dare to show themselves, but in the second cycle they are better and the attitude of responsibility is increasingly visible. Based on the data obtained, the ability to write an explanatory text summary using the SQ3R model with the aid of mind mapping increased. Abstrak: Penelitian ini bertujuan untuk meningkatkan kemampuan menulis ringkasan teks eksplanasi menggunakan model SQ3R berbantuan mind mapping. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK). Penelitian ini menggunakan siklus Arikunto dalam dua siklus. Teknik pengumpulan data pada penelitian ini adalah observasi, wawancara, tes, dokumentasi, dan catatan lapangan. Subjek penelitian ini adalah siswa kelas 5C SDN Polehan 2 Kota Malang. Instrumen penelitian menggunakan instrumen observasi guru dan siswa, instrumen wawancara, dan instrumen tes. Analisis data menggunakan analisis deskriptif kuantitatif dan kualitatif. Persentase rata-rata aktivitas guru dari siklus I sebesar 83.35 persen menjadi 95 persen pada siklus II. Persentase hasil belajar keterampilan pada pra tindakan sebesar 31.81 persen. Persentase hasil belajar keterampilan pada siklus I sebesar 86.36 persen, pada siklus II meningkat menjadi 90.9 persen. Pada aspek sikap pada siklus I masih kurang dalam aspek percaya diri dikarenakan siswa masih malu dan belum berani unjuk diri, namun pada siklus II sudah lebih baik serta sikap tanggung jawab semakin terlihat. Berdasarkan data yang didapatkan, kemampuan menulis ringkasan teks eksplanasi menggunakan model SQ3R berbantuan mind mapping meningkat.